Changes in B inhibitor and cytokinin levels in response to long wilting periods in grain sorghum at different growth stages : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science in Plant Science at Massey University - Tay Kee Chong, George (Massey University, 1976)
Plants of Sorghum bicolor L. Moench R.S. 610, a hybrid grain variety, were subjected to three water stress cycles during the following growth stages :- (i) Late vegetative stage (ii) Boot to bloom stage (iii) Dough stage. Water status of the plants was measured by pressure bomb and Weatherly and Barr s' method. Both β inhibitor and cytokinin activity in leaves and roots were determined by two bioassays a) wheat coleoptile and b) radish cotyledon respectively. The bioassays results were expressed as (±) abscisic acid and kinetin equivalents respectively. The results indicated that changes in levels and activity of ABA and cytokinin occurred in response to water stress. ABA levels in leaves increased rapidly up to 13 fold from the control to the maximum stress during the first and second stress cycles, while ABA levels of leaf samples from the third stress cycle only increased to 6 fold at the maximum stress period. In the roots, ABA levels did not increase markedly as the leaf samples in all the three stress cycles. Cytokinin contents in both leaves and roots changed qualitatively and quatitatively in response to severe stress. There was a general decline in cytokinin activity as the magnitude of stress increased. There was a shift of cytokinin activity in peak 2 to peak 1 as the stress periods prolonged. Grain yield, in terms of grain weight and grain number, was measured for the three stress cycles. The results showed that there were two 'critical' stages when sorghum plants were susceptible to stress that is a) late vegetative to early boot stage and b) during inflorescence development and flowering period. The involvement of abscisic acid and cytokinins in the plant's adaptation to water stressed was discussed.
Irregular pagination.
Keywords: Growth; Sorghum -- Effects of stress on; Plants, Effect of drought on; Sorghum -- Water requirements